A redox-activated theranostic nanoagent: toward multi-mode imaging guided chemo-photothermal therapy. Issue 33 (19th July 2018) - Zhang, Ting-Ting; Xu, Cong-Hui; Zhao, Wei; Gu, Yu; Li, Xiang-Ling; Xu, Jing-Juan; Chen, Hong-Yuan
Abstract : We construct a tumor redox microenvironment responsive core–shell therapeutic nanoagent for multi-mode imaging guided synergistic therapy in vitro and in vivo . Abstract : Development of tumor microenvironment responsive and modulating theranostic nano-systems is of great importance for specific and efficient cancer therapy. Herein, we report a redox-sensitive nanoagent combining manganese dioxide (MnO2 ) and gold nanoshell coated silicon nanoparticles for synergistic chemo-photothermal therapy of hypoxia solid tumors. In highly reducing tumor tissues, the outer MnO2 nanosheet with the loaded drug would be dissociated by intracellular glutathione (GSH), resulting in on-demand drug release, as well as generating Mn 2+ ions which provided high contrast magnetic resonance imaging (MRI), and fluorescence imaging (FI) in vitro and in vivo . While upon near-infrared (NIR) light irradiation, the gold nanoshell modulated the hypoxic tumor microenvironment via increasing blood flow, achieving enhanced photothermal therapy (PTT) and chemotherapy. After tail vein injection into tumor-bearing mice and monitoring in real time, the intelligent redox-activated nanoagent exhibited high tumor accumulation and powerful synergistic chemo-photothermal therapy efficiency. The proposed work developed a noninvasive strategy to modulate the tumor microenvironment and enhance the anticancer therapeutic effect. We believe that this single nano-platform exhibits promising potential as a comprehensive theranostic agent to enhance the efficacies of synergistic cancer therapy.